Social and Ontologic Aspects of the Concept «Information War» - Andrey Andreevich Kovalev (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article considers the socio-ontological aspects of the information war as a special kind of intellectual confrontation of civilizations in the modern era of globalization. Information warfare is an integral part of the active phase of geopolitical confrontations, acting as a gateway to the classical forms of political destructive actions. The ontology of information war assumes the possibility of a power confrontation of civilizations, but it comes only after the maximum easing of the psychic, emotional and strong-willed resources of enemy. Information war annihilates patriotism as a special way of worldview and attitude.